2015
DOI: 10.1093/ndt/gfv048
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of post-translational modifications in chronic kidney disease and cardiovascular disease

Abstract: Post-translational modifications (PTMs) of proteins and peptides have recently gained much attention, as they are involved in the pathogenesis of cardiovascular disease and eventually also play a role in the progression of chronic kidney disease (CKD). In this review, we provide an overview of post-translational protein modifications such as carbamylation, glycation and oxidation, starting with their definitions, mechanisms and clinical relevance in the setting of CKD and cardiovascular disease. The methods cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 96 publications
1
84
0
Order By: Relevance
“…At the proteomic level, differential levels of protein expression 253 and post-translational protein modifications resulting from altered gene expression or uraemic toxicity can be precisely defined, setting the stage for novel therapeutic approaches. For example, post-translational modifications that change protein half-life or function, such as carbamylation, or high levels of methylglyoxal-derived advanced glycation end-products have been identified in patients with uraemia 254 .…”
Section: A Systems Biology Approachmentioning
confidence: 99%
“…At the proteomic level, differential levels of protein expression 253 and post-translational protein modifications resulting from altered gene expression or uraemic toxicity can be precisely defined, setting the stage for novel therapeutic approaches. For example, post-translational modifications that change protein half-life or function, such as carbamylation, or high levels of methylglyoxal-derived advanced glycation end-products have been identified in patients with uraemia 254 .…”
Section: A Systems Biology Approachmentioning
confidence: 99%
“…Although isocyanate or thiocyanate produced under uremic conditions lead to carbamylation of amino acids and proteins but carbamylation of LDL is most relevant to the development of atherogenesis. Some other modifications of LDL have been identified that are linked to atherosclerotic plaque formation and progression [30]. Recent studies suggest that cLDL is a dominant form of modified LDL that occurs either by urea-derived cyanate or thiocyanate-derived cyanate generated by the enzyme MPO (myeloperoxidase) [4].…”
Section: Discussionmentioning
confidence: 99%
“…9,24,25 It has also recently been shown that eosinophil peroxidase-mediated carbamylation of proteins can alter immune responses and give rise to a triggering of inflammatory signals in a similar way as could be seen in asthma. An increased carbamylation of proteins in vivo has been seen in patients with chronic kidney disease, characterized by elevated levels of urea and cyanate in the circulation and a possible increased risk of atherosclerosis.…”
Section: Concentration Of Ica Mic and Hcn In Frying Fumes (μG/m 3 ) Bmentioning
confidence: 96%
“…An increased carbamylation of proteins in vivo has been seen in patients with chronic kidney disease, characterized by elevated levels of urea and cyanate in the circulation and a possible increased risk of atherosclerosis. 9,24,25 It has also recently been shown that eosinophil peroxidase-mediated carbamylation of proteins can alter immune responses and give rise to a triggering of inflammatory signals in a similar way as could be seen in asthma. 26 Furthermore, cyanates could react with, and covalently bind to, glutathione which is a major lung antioxidant that plays an important role for reducing oxidative stress and airway inflammation.…”
Section: Concentration Of Ica Mic and Hcn In Frying Fumes (μG/m 3 ) Bmentioning
confidence: 96%